(untitled) (Perner’s Contacts, 2007)
The paper solves a problem of escorts about the oversized-load-transportations in road-transport. An emphasis places especially on technical-escort. The Differences of choice representatives of member states of Europe Union, in legislation, duties and competences of escort-worker are presented in the paper. The solutions of standardization-process of the escort-vehicle-using-conditions in Europe Union are presented in conclusion